Identidades dispersas; uma nova sensibilidade : dos ativismos LGBT às ocupações estudantis de 2016 - Castello, Naiara Ferreira Vieira (2018)
This work began as a research proposal about sexual and gender minorities’ activism within the Federal University of Espírito Santo. Moved by the desire to discuss identity politics and its effects, in a period of rising conservatism, and, at the same time, of intensification of the struggles of minority movements, we sought, at first, to get to know the strategies of LGBT groups and individuals at the university, as well as to investigate the networks composed by them and the tensions provoked by their presence in the institutional policies. Adopting a cartographic posture as a methodological choice, we began to delineate the landscape of the research field from the LGBT collective Desviantes, which was formed in 2016. We followed the meetings and actions of the collective, paying attention to how the identity discourse emerged and specially to the way in which the possibilities of other means of alliances were forged – ones that did not presume similarity. During the course of the field research, faced with the impeachment of then-President Dilma Rousseff and with the student occupation movements that opposed to the austerity measures adopted by Michel Temer, the collective dispersed. Welcoming the twists and turns imposed by the field, we followed the dispersion of the group, and began, from then on, to think of the identities and other possibilities of alliances through the experiences of the occupations. In the university and in the occupied schools, we found clues pointing to the production of other modes of relation, coming from a situation of shared precariousness, which would be expressed by the emergence of a new sensibility, which is, in itself, revolutionary.